Hubungan Kecerdasan Emosional dengan Tingkat Empati dan Kecemasan pada Mahasiswa Fakultas Kedokteran Universitas Tanjungpura Angkatan 2020 - Jessica Juniarta Sihombing; Ita Armyanti; Agustina Arundina Triharja T (PT Kalbe Farma Tbk., 2023)
Background. Medical students as a future medical personnel needs empathy to understand patients. However, anxiety due to assignments and lectures can be a barrier in expressing empathy. Emotional intelligence can affect the application of empathy and in overcoming anxie`ty. Purpose. To search the relationship between emotional intelligence and the level of empathy and anxiety among students of Faculty of Medicine, Tanjungpura University, year 2020. Methods. A cross-sectional analytic study on Faculty of Medicine, Tanjungpura University students, year 2020 with total sampling technique. Data from 203 samples was obtained from filling in personal data, L-MMPI questionnaire, stressor sheet, emotional intelligence, JSE S-Version, JSE HPS-Version, and BAI. Spearman correlation test was used for analysis. Results. Hypothesis test results in relation with empathy: self-awareness (p = 0.050; r = 0.138), self-control (p = 0.109; r = 0.113), self- motivation (p = 0.000; r = 0.305), social awareness (p = 0.039; r = 0.14, and social skills (p = 0.025; r = 0.157). Hypothesis test results in relation with anxiety: self-awareness (p = 0,000; r = -0.250), self-control (p = 0.013; r = -0.174), self-motivation (p = 0.013; r = -0.174), social awareness (p = 0.006; r = -0.192), and social skills (p = 0.000; r = -0.243). Conclusion. There are significant positive relationships between self-awareness, self-motivation, social awareness, and social skills on levels of empathy; and significant negative relationship between self-awareness, self-control, self-motivation, social awareness, and social skills on levels of anxiety.